River basin management in the twenty-first century : understanding people and place - Squires, Victor Roy; Milner, Hugh Martin; Daniell, Katherine Anne (CRC Press/Taylor and Francis Group, 2014)
The mid-latitude regions of the world are those with the greatest development of agriculture industry, and with burgeoning demands on natural resources. Management of the rivers and the surrounding landscape is one of the important tasks for today and for the foreseeable future. Lessons learned from centuries of management (and mismanagement) have been distilled into principles and practices which form the subject matter for this book. It provides both a global perspective and an entrée to the special problems associated with management of transboundary rivers.
Keywords: Watershed management.; Watersheds.; elektronické knihy; electronic books